Redefining the Museum Experiences in the Virtual Age - Jadán Guerrero, Janio; Mendoza M.; Alvites-Huamaní C. (My University, 2023)
Technology has the potential to redefine museums, opening the opportunity of new ways to connect with visitors. In the pandemic, museums had to close their doors and in-person visits were canceled. In reaction to this reality, many museums rushed to generate digital tours of their works and collections. The creation and development of these visits were born from the need to continue with virtual visits to continue to bring the knowledge that these institutions house closer. Today a possible approach is to create hybrid experiences that utilize digital technology capable of enriching a physical visit to museums. In this context, this paper addresses three experiences developed in Ecuador: (1) The Spiral of Memory proposal developed at the National Museum of Ecuador (MUNA), (2) The Animals of Yesterday and Today proposal developed at the Smithsonian Virtual Museum and (3) Interactive Museums as Pedagogical Mediators, digital educational resources in virtual learning environments. The conclusion of these experiences led to the conclusion that museums are spaces of interaction that contain an infinity of resources that allow children to create their own stories and compositions from the observation of real facts and situations, presented through the creation of physical or virtual experiences in these cultural spaces. © 2023, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.
Keywords: 5G terminals; Energy harvesting; Hybrid system; Radiofrequency; Solar